Evaluation of the National Health Insurance Program of Nepal: are political promises translated into actions? - Geha N. Khanal; Bishal Bharadwaj; Nijan Upadhyay; Tulasi Bhattarai; Minakshi Dahal; Resham B. Khatri (BMC, 2023)
Abstract Background Despite political promise to reduce out-of-pocket (OOP) expenditure on healthcare through the National Health Insurance Program (NHIP) of Nepal, its implementation is challenging with low enrolment and high drop-out rates. Program performance can often be linked with political economy considerations and interests of stakeholders. This study aimed to develop an in-depth understanding of organizational and systemic challenges in implementing NHIP. Methods We conducted a structured narrative review of available literature on the NHIP in Nepal. We analysed data using a political economy analysis for health financing reform framework. The findings were explained under six broad categories: interest groups, bureaucracy, budgets, leadership, beneficiary and external actors. In addition, we triangulated and further presented the literature review findings using expert opinions (views expressed in public forums). Results Nepal has formulated acts, rules, regulations, and policies to implement NHIP. Under this program, the Health Insurance Board (HIB) is the purchaser of health services, and health facilities under the Ministry of Health and Population (MoHP) are the providers. The NHIP has been rolled out in all 77 districts. Several challenges have hindered the performance of NHIP at the policy and implementation levels. Challenges under interest groups included inadequate or delayed reimbursement and drop-out of hospitals in implementing the programme. Bureaucracy-related challenges were hegemony of provider over the purchaser, and inadequate staff (delay in the approval of organogram of HIB). There was inadequate monitoring of premium collection, and claim reimbursement was higher than collected premium. Challenges under leadership included high political commitments but weak translation into action, consideration of health insurance as poor return on investment, and intention of leaders to privatize the NHIP. Beneficiaries experienced compromised quality of care or lack of services when needed, high drop-out rates and low interest in renewal of premiums. External actors provided technical assistance in policy design but limited support in implementation. Conclusions Despite enabling a policy environment, the NHIP faced many challenges in implementation. There is an urgent need for institutional arrangements (e.g. digitalization of claims and reimbursement, endorsement of organogram of HIB and recruitment of staff), increased coverage of financial protection and service (increased benefit package and introduction of cost-sharing/co-payment model), legislative reforms (e.g. legal provision for cost-sharing mechanism, integration of fragmented schemes, tripartite agreement to reimburse claims and accreditation of health facilities to ensure quality healthcare), and leveraging technical support from the external actors. High levels of commitment and accountability among political leaders and bureaucrats are required to strengthen financial sustainability and implementation.